Barriers to Male Involvement in Antenatal Care in Rural Mozambique. (October 2016) - Audet, Carolyn M.; Chire, Yazalde Manual; Vaz, Lara M. E.; Bechtel, Ruth; Carlson-Bremer, Daphne; Wester, C. William; Amico, K. Rivet; Gonzaléz-Calvo, Lázaro
Low rates of antenatal care (ANC) service uptake limit the potential impact of mother-to-child HIV-prevention strategies. Zambézia province, Mozambique, has one of the lowest proportions of ANC uptake among pregnant women in the country, despite the availability of free services. We sought to identify factors influencing ANC service uptake (including HIV counseling and testing) through qualitative methods. In addition, we encouraged discussion about strategies to improve uptake of services. We conducted 14 focus groups to explore community views on these topics. Based on thematic coding of discourse, two main themes emerged: (a) gender inequality in decision making and responsibility for pregnancy and (b) community beliefs that uptake of ANC services, particularly, if supported by a male partner, reflects a woman's HIV-positive status. Interventions to promote ANC uptake must work to shift cultural norms through male partner participation. Potential strategies to promote male engagement in ANC services are discussed.